1999
DOI: 10.1084/jem.190.9.1309
|View full text |Cite
|
Sign up to set email alerts
|

T Helper 1 Cells and Interferon γ Regulate Allergic Airway Inflammation and Mucus Production

Abstract: CD4 T helper (Th) type 1 and Th2 cells have been identified in the airways of asthmatic patients. Th2 cells are believed to contribute to pathogenesis of the disease, but the role of Th1 cells is not well defined. In a mouse model, we previously reported that transferred T cell receptor–transgenic Th2 cells activated in the respiratory tract led to airway inflammation with many of the pathologic features of asthma, including airway eosinophilia and mucus production. Th1 cells caused inflammation with none of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
157
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(178 citation statements)
references
References 56 publications
16
157
2
3
Order By: Relevance
“…Although other parameters of allergic inflammation, such as eosinophil recruitment to airways, were significantly augmented in Treg-depleted DEREG mice, there was no statistically significant difference observed in mucus production across groups of WT or DEREG mice that were sensitized and challenged with OVA, whether in the presence or absence of Treg in the latter groups. By transfer of in vitro differentiated Th1 and Th2 cells, Cohn et al have shown that mucus production by epithelial cells and recruitment of eosinophils to the airways are controlled by different mechanisms [27]. Hence, there is a possibility that Treg do not influence the pathway involved in mucus production under conditions employed in our study regimen.…”
mentioning
confidence: 72%
“…Although other parameters of allergic inflammation, such as eosinophil recruitment to airways, were significantly augmented in Treg-depleted DEREG mice, there was no statistically significant difference observed in mucus production across groups of WT or DEREG mice that were sensitized and challenged with OVA, whether in the presence or absence of Treg in the latter groups. By transfer of in vitro differentiated Th1 and Th2 cells, Cohn et al have shown that mucus production by epithelial cells and recruitment of eosinophils to the airways are controlled by different mechanisms [27]. Hence, there is a possibility that Treg do not influence the pathway involved in mucus production under conditions employed in our study regimen.…”
mentioning
confidence: 72%
“…An important contribution to the understanding of the role of allergy and Th2 cells in asthma has also benefited from mouse models of allergic asthma. Adoptive transfer of allergen-specific Th2 cells generated from ovalbumin (OVA)-specific T-cell antigen receptor-transgenic DO11.10 mice results in the development of AHR and airway inflammation (65), whereas the transfer of allergen-specific Th1 cells results in a diminution of airway eosinophilia and mucus production (66). These models greatly enhanced the knowledge on the involvement of Th2 cells in allergic inflammation, but reflected only the allergen-driven pathway of asthma.…”
Section: The Th2 Hypothesis In Asthmamentioning
confidence: 82%
“…Immune deviation strategies have been proposed for other Th2-mediated diseases including allergy and asthma. 7,[37][38][39][40] The results presented here suggest that the ultimate success of these strategies will rely not only on the successful establishment of a type-1-dominant response, but also on the simultaneous and efficient activation of NOS-2 expression in downstream effector populations. Indeed, it is intriguing to speculate that the previously reported inability of Th1 cells to modulate Th2-mediated inflammation 38,39 may be due entirely to the inefficient activation of NOS-2 at sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%